See MIPS run - Sweetman, Dominic. (Morgan Kaufmann Publishers/Elsevier, 2007)
This second edition is not only a thorough update of the first edition, it is also a marriage of the best-known RISC architecture--MIPS--with the best-known open-source OS--Linux. The first part of the book begins with MIPS design principles and then describes the MIPS instruction set and programmers’ resources. It uses the MIPS32 standard as a baseline (the 1st edition used the R3000) from which to compare all other versions of the architecture and assumes that MIPS64 is the main option. The second part is a significant change from the first edition. It provides concrete examples of operating system low level code, by using Linux as the example operating system. It describes how Linux is built on the foundations the MIPS hardware provides and summarizes the Linux application environment, describing the libraries, kernel device-drivers and CPU-specific code. It then digs deep into application code and library support, protection and memory management, interrupts in the Linux kernel and multiprocessor Linux.